Glycocalyx breakdown is associated With severe disease and fatal outcome in Plasmodium falciparum malaria - Yeo, Tsin Wen (2021)
Background: Interactions between the endothelium and infected erythrocytes play a major role in the pathogenesis of falciparum malaria, with microvascular dysfunction and parasite sequestration associated with worsening outcomes. The glycocalyx is a carbohydrate-rich layer that lines the endothelium, with multiple roles in vascular homeostasis. The role of the glycocalyx in falciparum malaria and the association with disease severity has not been investigated.